Synthesis, characterization, antioxidant activity and anticancer activity of l-phenyl alanine -bis-mandelate - S. USHA; CHARLES KANAKAM CHRISTOPHER (International Journal of Pharma and Bio Sciences, 2017)
The stress and strain experienced physically and mentally with the intake of insufficient unhealthy food give age related health problems. The unhealthy diet consumption and irregular intake of on time food habit of human beings are giving the formation of reactive oxygen species (ROS). The diseases caused by the food habits, routine stress and strain can be tackled by scavenging the ROS immediately after the formation. Small organic molecules possessing donor-acceptor functional groups are resulting in the formation of hydrogen bonding interactions which stabilises the molecular structure. The weak vander Waals forces of attraction and charge transfer mechanisms are resulting in the formation of low energy gap organic salts with high chemical reactivity and low chemical stability. These salts showed high antioxidant activity, high antiradical power and the presence anticancer property. Synthesised novel organic salt, L-phenyl alanine- bismandelate (BMALPA), the title compound, by the combination of mandelic acid (MA) and L-phenyl alanine (LPA) in the molar ratio 2:1 in the aqueous medium. The characterisation studies, determination of antioxidant activity by chemical and electrochemical methods and in vitro anticancer property using liver carcinoma cell line HepG2 and normal Vero cell line of the title compound showed its promising ability to act as an anticancer material due to the presence of increase in number of hydroxyl groups.